Validation of a coupled electromagnetic and thermal model for estimating temperatures during magnetic nanoparticle hyperthermia. (1st January 2021) - Kandala, Sri Kamal; Sharma, Anirudh; Mirpour, Sahar; Liapi, Eleni; Ivkov, Robert; Attaluri, Anilchandra
Abstract: Purpose: Alternating magnetic field (AMF) tissue interaction models are generally not validated. Our aim was to develop and validate a coupled electromagnetic and thermal model for estimating temperatures in large organs during magnetic nanoparticle hyperthermia (MNH). Materials and methods: Coupled finite element electromagnetic and thermal model validation was performed by comparing the results to experimental data obtained from temperatures measured in homogeneous agar gel phantoms exposed to an AMF at fixed frequency (155 ± 10 kHz). The validated model was applied to a three-dimensional (3D) rabbit liver built from computed tomography (CT) images to investigate the contribution of nanoparticle heating and nonspecific eddy current heating as a function of AMF amplitude. Results: Computed temperatures from the model were in excellent agreement with temperatures calculated using the analytical method (error < 1%) and temperatures measured in phantoms (maximum absolute error <2% at each probe location). The 3D rabbit liver model for a fixed concentration of 5 mg Fe/cm 3 of tumor revealed a maximum temperature ∼44 °C in tumor and ∼40 °C in liver at AMF amplitude of ∼12 kA/m (peak). Conclusion: A validated coupled electromagnetic and thermal model was developed to estimate temperatures due to eddy current heating in homogeneous tissue phantoms. The validated model was successfully used to analyze temperature distribution in complex rabbit liver tumor geometry during MNH. In future, model validation should be extended to heterogeneous tissue phantoms, and include heat sink effects from major blood vessels.